Herbal medicinal products in RESPIRATORY diseases – STANce of the Polish PHYTOtherapy Association – STANPHYTO RESPIRATORY II - Doniec, Zbigniew; Krauze-Baranowska, Mirosława; Czerwionka-Szaflarska, Mieczysława; Kuchar, Ernest; Fecka, Izabela; Sybilski, Adam; Woroń, Jarosław; Mastalerz-Migas, Agnieszka (Family Medicine & Primary Care Review, 2023)
The paper reviews herbal medicinal products used in infectious diseases of the respiratory tract. Due to the multidirectional effects of the biological action of the contained herbal active substances (anti-inflammatory, antioxidant, antimicrobial, antitussive, diuretic and others), they have the properties that alleviate the severity of symptoms, reduce their frequency and, consequently, shorten the duration of the disease, as well as reduce the risk of complications. Some of them have additional immunomodulatory properties, supporting natural immune mechanisms.